Assessing a social responsibility model for sustainable company growth in the Fourth Industrial Revolution. Issue 3 (13th September 2019) - Park, Sung Hyun; Shin, Wan Seon; Kim, Kwang Jae
Abstract : Purpose: The Fourth Industrial Revolution ( 4th IR) affects the mode of company management. This paper aims to present a revised social responsibility (SR) model as an evaluation tool for corporate social responsibility (CSR) performance for sustainable organizational growth in the era of the 4th IR. Design/methodology/approach: To develop an SR model that can be used well in the era of the 4th IR, the key references are "ISO 26000: Guidance on Social Responsibility" and the "Global Reporting Initiative (GRI) Guidelines." For International Organization for Standardization (ISO) 26000 and the GRI guidelines, see the homepages in the References section. On the basis of these guidelines, a new SR model for sustainable development in the 4th IR is developed in this paper. Findings: For a new SR model in the 4th IR, the concepts of management quality (MQ), quality responsibility (QR), creating shared value (CSV), social value and open data and open quality management are incorporated into the existing ISO 26000 evaluation criteria. Originality/value: The 4th IR is changing the concepts of both quality management (QM) and SR. To the best of the authors' knowledge, the new concept of SR has yet to be discussed extensively. In this paper, a new SR model is suggested to reflect the characteristics of the 4th IR.